UNILATERAL CHOANAL ATRESIA IN ADULT: A CASE REPORT - Jovanović, Anđelina (Halo 194 Scientific Journal of Emergency Medicine, 2023)
Introduction           Case report          Conclusion
Keywords: unilateral choanal atresia, congenital, septal deviation